A case of severe aortic stenosis caused by unicuspid unicommissural aortic valve. Issue 4 (October 2020) - Tanabe, Junya; Sato, Hirotomo; Endo, Akihiro; Yoshitomi, Hiroyuki; Shimizu, Koji; Oda, Teiji; Tanabe, Kazuaki
Abstract: Unicuspid aortic valve (UAV) is an extremely rare congenital malformation that frequently presents with valvular dysfunction or aortic aneurysm. Here we report the case of a 49-year-old man with severe aortic stenosis caused by UAV requiring the Bentall procedure. Two- and three-dimensional transesophageal echocardiography revealed an eccentric opening in an aortic valve and a lateral attachment to the aorta at the orifice level, suggestive of which is consistent with unicommissural UAV as conﬁrmed by surgical ﬁndings. <Learning objective: We report a rare case of unicuspid aortic valve (UAV) requiring the Bentall procedure. This case demonstrates the utility of two- and three-dimensional transesophageal echocardiography in revealing the morphology of UAV, as conﬁrmed by surgical ﬁndings.>